Renewable energy production based on solar power and magnetic field prototype in Bangladesh - Ohirul Qays; Farhana Yasmin (International Journal of Applied Power Engineering (IJAPE), 2020)
Though modern technology of new era is mostly dependent on power sector entirely, the current energy scenario is showing a serious negative effect for the last few decades. Comparatively, Bangladesh is facing a precarious effect because of the scarcity of fossil-fuel dissipation. To accomplish the power demand resolution, a new type of power generation is proposed in this research paper. Magnetic flux and solar irradiation is combined to get maximum power outcome. The PV panel supplies the maximum power in the peak solar radiation and terminates the energy stream at night time. However, the floating generator can supply its maximum creation day or night time according to the movement of water wave tendency. For this reason, a PV-floating Generator based integrated renewable energy scheme is inspected in this venture. The experimental result shows its real-world validation (Maximum 14.5 Watt output) comparing to conventional methods.